Novel Candidate Single Nucleotide Polymorphisms of ERCC2 Gene that Influence Colorectal Cancer Susceptibility - Rand Farhad; Eman Saadi Saleh; Ahmed Zuhair Alsammarraie (College of Pharmacy University of Baghdad, 2024)
Colorectal cancer (CRC) is the most common gastrointestinal malignancy and one of the top ten common cancers worldwide with approximately 2 million cases. There are multiple risk factors that could lead to CRC emergence; of which are genetic polymorphisms. Excision repair cross-complementing group 2 (ERCC2) gene encodes for ERCC2 enzyme which plays a crucial role in maintaining genomic integrity by removing DNA adducts. Several studies suggested that there could be a link between genetic polymorphisms of ERCC2 gene and the risk of CRC development. Hence the present study aims to validate the relationship between the following ERCC2 single nucleotide polymorphisms (rs13181, rs149943175, rs530662943, and rs1799790) and CRC susceptibility. A total of 121 participants were enrolled in this case control study; 72 CRC patients and 49 apparently healthy individuals. Genotyping was performed using polymerase chain reaction (PCR) followed by sequencing then the association between genetic polymorphisms and CRC susceptibility was examined. GA genotype and A allele of rs149943175 were associated with lower risk of CRC development. However, GA genotype and A allele carriers of rs530662943 had significantly increased risk compared to GG genotype. Additional stratified analyses showed that carriers of heterozygous genotype of rs149943175 who non-smokers, females or BMI figures less than 25 are less likely to develop CRC compared to wild genotype carriers. Taken together, genetic polymorphisms of ERCC2 modulate the susceptibility of CRC malignancy.